DSAP: A Protocol for Coordinated Spectrum Access - Bahl, Victor; Brik, Vladimir; Rozner, Eric; Banerjee, Suman (IEEE Dynamic Spectrum Access Networks (DySPAN), 2005)
The continually increasing number of wireless devices operating in the unlicensed frequency bands makes the freely-available wireless spectrum a scarce commodity. Under such circumstances, efficient wireless spectrum management is necessary to minimize the effects of overcrowding and maximize quality of service. In this paper we present the design, implementation and evaluation of Dynamic Spectrum Access Protocol (DSAP), a centralized method for managing and coordinating spectrum access.